Stabilisation of Laterite Soils With Cement and Metakaolin - Paul Kakooza (Uganda Christian University, 2024)
The research carried out was aimed at improving the properties of the laterite soils while using cement and metakaolin in the subbase soil layer. The research was guided by three specific objectives which included determining the engineering properties of the neat soils, determining the properties of the metakaolin and determining the engineering properties of the cement-metakaolin stabilized laterite soil. The case study of the research was Jambula road located in Entebbe municipality and the metakaolin was got from Buwambo. Furthermore, the study discussed about the sampling and preparation of the materials used. Different laboratory tests were carried out at Sterling laboratory while following the specific objectives stated in reference with the required standards of British Standards, General Specification MOW and others. Different tests of CBR, MDD, PI and UCS were carried out on the stabilized cement-metakaolin laterite soil and at optimum cement and metakaolin content of 3% and 4%, the mix had an MDD value of 2.071gm/cm³, CBR value of 57%, Pi value of 13.1% and USC value 1.41Mpa which all lied in the required range for a subbase soil layer in accordance with Ministry of works and Transport. Hence making cement and metakaolin good chemical stabilizers for the laterite soils. For this research, some conclusions were drawn and as well recommendations for further research were given.